EFFECTIVENESS OF HERBAL AND NON-HERBAL TOothpaste TO DECREASE PLAC INDEX IN CLASS IV STUDENTS AT SD NEG E RI 62 COT MESJID, BANDA ACEH - Cut Aja Nuraskin; Intan Dwi Addilla; Reca (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Plaque is an organic deposit that is an indicator of dental and oral hygiene. The emergence of dental plaque can be prevented by taking preventive measures, namely by brushing teeth accompanied by the use of toothpaste. In the market, there are various toothpaste products with various brands with various compositions. Among them is toothpaste with ingredients that contain herbs and toothpaste that does not contain herbs. The herbal content in toothpaste is expected to inhibit plaque growth because it is related to the ability of herbal ingredients to inhibit microbial growth. The purpose of this study was to determine the effectiveness of herbal and non-herbal toothpaste in reducing plaque index. This research method is quasi-experimental with pretest and posttest. A sample of 46 respondents was obtained using the Slovin formula and divided into 2 groups, namely group I for herbal toothpaste with 23 respondents and group II for non-herbal toothpaste with 23 respondents. The plaque index was measured using the PHP-M (Personal Hygiene Performance Modified) method. Paired t-test was used to determine differences in dental plaque index before and after treatment. Results The average plaque index after using herbal toothpaste and after using non-herbal toothpaste was 30.35 and 34.78. Dependent sample t-test analysis showed that the mean difference in plaque index in the two groups was 4.43. Conclusion: there is a big average difference between the two variables above or the use of herbal toothpaste is better than non-herbal toothpaste based on the PHP-m index value and the use of herbal toothpaste is better for lowering the PHP-m index. (CI 90% p= 0.092).